Pengaruh Pertumbuhan Penjualan, Kinerja Lingkungan, Industri, dan Komitmen Terhadap Pengungkapan Emisi Karbon - Nur Hidayati; Ahmad Nurkhin; Satsya Yoga Baswara (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
This study aims to examine the factors that influence carbon emission disclosure in LQ45 Index companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The research population comprised 62 LQ45 companies, from which 25 companies were selected through purposive sampling, resulting in 100 units of analysis. Data were obtained through documentation techniques using secondary data sources. The analysis methods include descriptive analysis, regression assumption tests (comprising regression data tests, classical assumption tests, hypothesis testing, and Moderated Regression Analysis), and additional testing using robust regression. All statistical analyses were conducted using Eviews version 12. The findings show that sales growth and industry type do not have a significant effect on carbon emission disclosure. In contrast, environmental performance has a significant positive effect on carbon emission disclosure. Furthermore, environmental commitment acts as a moderating variable that strengthens the relationship between the influencing factors and carbon emission disclosure. The study recommends that future research consider additional relevant variables and expand the scope to include other sectors beyond the LQ45 Index. It also encourages companies with high sales growth and those in carbon-intensive industries to increase their carbon emission disclosure as part of their environmental responsibility.